KUALITAS PELAYANAN ADMINISTRASI AKADEMIK DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TADULAKO - Amrizal, Alfianto (Katalogis, 2016)
This study aims at determining the quality of academic services at Teacher Training and Education Faculty of Tadulako University. This research is designed qualitatively. Informants of this research are Vice Dean of Academic Fields, Head of Administration, Head of Student Guidance and Officer of Sub-Division of Student Affairs and students of Teacher Training and Education Faculty who were determined using purposive sampling with data collection methods consisted of observation, interview and documentation. As for the technical analysis of the data including data collection, data reduction, data presentation, and conclusion. The results shows that, (1) Quality of academic services at Teacher Training and Education Faculty, of responsivenes is already quite good, although not yet optimal, it is in because the number of employees by the number of students that are not comparable, because the number of employees who lack that causes academic administrative services in FKIP UNTAD be disturbed / retarded. (2) Quality of academic services at Teacher Training and Education Faculty, perceived from assurance, has been good, they show this by storing the data files of students with a neat either manually or by the application SIAKAD (Academic Information System). However of friendly and patience of the employees in the administration of academic/student still less friendly and patient in serving the students, they sometimes get angry and sometimes the students were told to wait a long time without any definite cause (3) Quality of academic services at Teacher Training and Education Faculty perceived from the tangible is not qualified for the students to feel physically, the quality of service provided by the service providers is , it is also not yet adequate by the employees / staff of academic administration. (4) Quality of academic services at Teacher Training and Education Faculty seen from empathy is still not perceived by the students, because the workers only focused to serve students in the management of academic and rarely provide the motivation that makes the student spirit in teaching, learning and lectures. (5) Quality of academic services at Teacher Training and Education Faculty viewed from reliability not maximized and students still often complain about the slow service at FKIP, it is recognized by the Vice Dean for Academic Affairs, this is because the number of staff/employee who is not professional with the number of students, this is slowing down the process of service, and the clerks never complicate the students is care of some things, because it's all been in accordance with existing rules and are in accordance with the Standard Operating Procedure (SOP) in FKIP.